Tatalaksana Terapi Stroke Hemoragik Pada Hipertensi Grade II Di Ruang ICU RSD Gunung Jati Kota Cirebon - Afriani, Julia; Muadi; Zakiyah, Vivy; Azriliyani, Raeisya; Rahmawati, Yulia (MEJORA Medical Journal Awatara, 2024)
Hemorrhagic stroke is a type of stroke caused by rupture of blood vessels in the brain, resulting in bleeding in the brain. The main risk factor that can influence a stroke is hypertension. This study aims to provide a picture of the implementation of nursing care for patients with hemorrhagic stroke using a nursing process approach. This research uses qualitative methods. The type of case study used in this research is a prospective case study. This research was carried out at RSD Gunung Jati, Cirebon City, precisely in the ICU room on March 1 2024. Data collection techniques were through observation, interviews and Further documentation studies use data analysis. After providing nursing care to the patient with management of hemodynamic stability for 3 x 24 hours, given therapy, the results showed that the patient’s blood pressure was stable 150/95mmhg, the patient’s consciousness was sopor GCS 6 and the muscle strenght of the right upper lower extremity was 0 in the patient’s.